The Influence of the Reference Area of Aileron on the N2XX Aircraft Using Computational Fluid Dynamics - Rahmah, Siti Nur; Jatisukamto, Gaguk; Sutjahjono, Hary (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
Aileron is a control surface that functions as a regulator of roll motion. The movements of the ailerons are opposite to the left and right sides. Previous studies have shown that graphs of hinge moment coefficient (Chm) values increases with increasing angle of attack. This study is to determine the aerodynamic characteristics of aileron by combining the surface area of the vane into the aileron by varying the aileron’s deflection. The calculation is performed using a numerical method in two dimensions (2D) commercial CFD simulation software. The results of the study concluded that the hinge moment coefficient for modified airfoil at δA = -20°, 0°, and 20° was -0.071, 0.078, and 0.177, respectively. These values are smaller when compared to Chm value in basic aileron that was -0.094, 0.095, and 0.201, respectively.